Cellular transformations in near‐infrared light‐induced apoptosis in cancer cells revealed by label‐free CARS imaging. Issue 12 (13th August 2019) - Levchenko, Svitlana M.; Kuzmin, Andrey N.; Pliss, Artem; Ohulchanskyy, Tymish Y.; Prasad, Paras N.; Qu, Junle
Abstract: Photobiomodulation (PBM) involves light to activate cellular signaling pathways leading to cell proliferation or death. In this work, fluorescence and Coherent anti‐Stokes Raman Scattering (CARS) imaging techniques were applied to assess apoptosis in human cervical cancer cells (HeLa) induced by near infrared (NIR) laser light (808 nm). Using the Caspase 3/7 fluorescent probe to identify apoptotic cells, we found that the pro‐apoptotic effect is significantly dependent of irradiation dose. The highest apoptosis rate was noted for the lower irradiation doses, that is, 0.3 J/cm 2 (~58%) and 3 J/cm 2 (~28%). The impact of light doses on proteins/lipids intracellular metabolism and distribution was evaluated using CARS imaging, which revealed apoptosis‐associated reorganization of nuclear proteins and cytoplasmic lipids after irradiation with 0.3 J/cm 2 . Doses of NIR light causing apoptosis (0.3, 3 and 30 J/cm 2 ) induced a gradual increase in the nuclear protein level over time, in contrast to proteins in cells non‐irradiated and irradiated with 10 J/cm 2 . Furthermore, irradiation of the cells with the 0.3 J/cm 2 dose resulted in lipid droplets (LDs) accumulation, which was apparently caused by an increase in reactive oxygen species (ROS) generation. We suggest that PBM induced apoptosis could be caused by the ability of NIR light to trigger excessive LDs formation which, in turn, induces cellular cytotoxicity. Abstract : In this study, CARS imaging was used to examine the near‐infrared (NIR) light effect on proteins and lipids metabolic processes during the photobiomodulation (PBM)‐induced apoptosis in HeLa cells. The distinct dose‐dependent changes in proteins/lipids content and distribution, featuring the progression of cellular apoptosis induced by 808 nm NIR light irradiation were demonstrated. As a result, the mechanism of apoptosis induced by PBM in HeLa cells was proposed.